Overview of Management of Salt Affected Soils in India - J.S.P.YADAV, (Journal of Soil and Water Conservation, 2022)
The world population that crossed6 billion in 2000, is expected to approach 11 billion by 2100, and the global demand for food, fiber and bio- energy products will grow at the annual rate of 25% and that of developing countries at 3.7% (FAO, 1993) as against the annual growth of only 1 % in the output. Out of the total land area of 13.5 billion ha in the world, roughly 3.03 billion ha (22%) is potentially cultivable, of which only one half (1.5 billion ha) is actually cultivated at different levels of productivity due to certain constraints. Therefore, very limited land is available for cultivation. In comparison to the global scenario, the situation in India is grimmer with a geographical area of 329 M ha(2.3% of total world’s land), supporting about 18 % human population and 15 % livestock population. The per capita arable land is only 0. 15 ha and the figure is expected to come down to 0.08 ha by 2025.